(untitled) - Japan institute for social and economic affairs (Tokyo, 1986)
This book introduce about trade, international economic policy, industry and technology, mamagement and labor and finance of Japan.
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan